Penatalaksanaan Fisioterapi Pada Kasus Trigger Finger Di RSUD Dr. Moewardi Surakarta - Fauzan, Miftah; , Arif Pristianto, SSt.FT.,M.Fis (2015)
Background: Trigger finger is a painful snapping phenomenon that occurs as the finger flexor tendons suddenly pull through a tight A1pulley portion of the flexor sheath.Trigger finger occurs in the tendons of the fingers which could cause changes inthe functionof the hand. This condition is characterized by a painful hand grasp or the presence of a trigger finger during finger flexion or extension movements. In many cases, the finger can remain blocked in a flexion or extension position and requires an external force for passively bringing it back into a neutral position. Aims of Research: To know the benefits of ultrasound therapy and exercise therapy modalities of pain reduction, increase range of motion, and increase muscle strength in the case of trigger finger. Result: After terapy for about six times the obtained result reduction in the degree of pain, in painful slience T1: 1 to T6: 0, tenderness T1: 5 to T6: 4, and motion pain T1: 6 to T6: 3. Increase range of motion of the metacarpophalangeal joint T1:S 100-00-500 to T6: S 100-00-750, proximal interphalanx joint T1: S 00-00-200 to T6: S 00-00-300, distal interphalanx joint T1: S 00-00-150 to T6: S 00-00-200. An increase in extensor metacapophalangeal muscle strength T1: 3+ to T6: 4-, flexor proximal interphalanx T1: 3+ to T6: 4-,flexor distal interphalanx T1: 3+ to T6: 4-, flexor metacarpophalangeal T1: 3+ to T6: 3+. Conclusion: Ultrasound therapy and exercise therapy can reduce pain, increase the range of motion, and increase muscle strength.